Authentic assessment of student learning outcomes : assessment of learning 2 - Navarro, Rosita L.; De Guzman- Santos, Rosita (Quezon City, Philippines : Lorimar Publishing, Inc., 2013)
This book introduces the topic of Authentic Assessment to would be teachers. It is an introductory textbook despite its title: Authentic Assessment of Student Learning Outcomes (Assessment 2). It covers nine chapters, all of which serve to elucidate the finer concepts that underlie authentic assessment, This book, together with its companion textbook (volume 1) can be comfortably covered in a one-semester.
Foreword -- Preface and Acknowledgment -- A Close Look at Student Learning Outcomes (SLO) -- Authentic Assessment: Meaning, Characteristics and Principles -- Authentic Assessment Tools -- Process-Oriented Performance-Based Assessment -- Product-Oriented Performance Based Assessment -- Assessment in the Affective Domain -- Portfolio Assessment Methods -- Grading and Reporting -- The Use of Statistics in Outcomes Assessment.
Includes bibliographical refrences.
Keywords: EDUCATION TEST AND MEASUREMENTS -- PHILIPPINES